Research on the application of weighted-Laguerre-FDTD method with “unidirectional explicit” matrix in cylindrical structure - Dawei ZHU; Hailin CHEN; Zhongwen SHEN; Xiuling JIA; Zhen LI (Tongxin xuebao)
To solve the shortcomings of FDTD algorithm in electromagnetic wave propagation in communication applications.A FDTD algorithm under “unidirectional explicit” matrix was constructed and applied to cylindrical structure.Firstly, a new coefficient matrix was established by the ideology of WCS and WLP.Secondly, the perturbation terms were introduced to form the initial value and iterative equations.Finally, the fields on the z axis were treated in special way.Numerical examples prove that the proposed algorithm is superior to the WCS-FDTD and WLP-FDTD in electromagnetic wave propagation.The best improvement efficiency is 83%, accuracy is 88%, and memory consumption is reduced by 44%.Meanwhile, comparing with the conventional FDTD algorithm, it can improve the efficiency of 7 time steps size and reduce the memory consumption by 53% without losing accuracy.Moreover, under the boundary truncation of the PML, the proposed algorithm also shows good electromagnetic wave energy absorption performance, which can reach below -60 dB.